Relief Aksara Bali (Reaksi) Berbantuan Suara untuk Pemberdayaan Anak Tunanetra dalam Literasi Aksara Bali di SLB Negeri 1 Tabanan - Sudiartini, Ni Pande Kadek Dewi; Utami, Ni Kadek Trisna Putri; Widianita, Ni Kadek Feby; Wulandari, Ni Kadek Ayu Gita; Widianingsih, Desak Made Dian; Sujana, I Wayan (Pelita Masyarakat, 2024)
The difficulty of teachers at SLB Negeri 1 Tabanan in teaching reading and writing Balinese script literacy to blind children has resulted in the low Balinese literacy skills of blind children at that school. To maximize learning of Balinese script, it is necessary to use learning media that suits the characteristics of blind children. This program aims to improve the ability of teachers to teach Balinese script using voice-assisted Balinese Script Relief (Reaksi) media so that it can increase Balinese script literacy and foster a competitive spirit in blind children. The method for implementing this activity consists of preparation, implementation (training and mentoring for 20 times), and evaluation. Evaluation data collection was carried out using observation and questionnaire methods. The result of the program is that there is an increase in teachers' ability to teach Balinese script using voice-assisted Reaksi media to blind children, from initially quite good to very good. Apart from that, there has been an increase in the learning outcomes of blind children who were initially less than good. It can be concluded that through the training program, the use of voice-assisted Reaksi can improve teachers' abilities in teaching Balinese script so that the reading and writing literacy of Balinese script for blind children also increases.